Coelindroma Kramer (Hemiptera: Cicadellidae: Neocoelidiinae) from Brazil: description of two new species and new record of C. fungosa - Gonçalves, Clayton Correa; Marques-Costa, Ana Paula; Ale-Rocha, Rosaly (Zootaxa, 2012)
Two new species of Coelindroma Kramer,1967: Coelindroma cornuta sp. nov. and Coelindroma tuberculata sp. nov. aredescribed and illustrated. C. cornuta sp. nov. can be distinguished from the other species of the genus by the aedeaguswith pair of long apical divergent processes; while C. tuberculata sp. nov. can be distinguished by the aedeagus with pairof short apical convergent processes. C. fungosa Kramer, 1967 is recorded from Brazil and an identification key to males of the species is provided.